Are exercise-induced changes of fatty acids associated with cardiac hypertrophy in athletes? A pilot study - Abdollahi Ensiyeh; Nikanfar Saba; Zolfaghari Mohammad Reza; Fattahi Amir (Sciendo, 2021)
Study aim: In this study, we evaluated the effects of acute and chronic exercise on the plasma FAs and their association with cardiac hypertrophy indices.